2015
DOI: 10.1111/aab.12196
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of antagonistic Bacillus and Pseudomonas strains for biocontrol potential and suppression of damping‐off and root rot diseases

Abstract: Novel strains of rhizobacteria, Pseudomonas fluorescens Pf 9A-14, Pseudomonas sp. Psp. 8D-45 and Bacillus subtilis Bs 8B-1, showed broad-spectrum antagonistic activity and provided suppression of Pythium damping-off and root rot of cucumber. Their biocontrol potential was further investigated for suppression of additional seedling diseases of cucumber (Phytophthora capsici) and radish (Rhizoctonia solani). Bacterial strains were also characterised for production of antibiotics, metabolites, volatiles, phytohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 66 publications
1
35
0
3
Order By: Relevance
“…Different lowercase letters above the bars indicate significant difference between the treatments at P < 0.05 level by ttest Many studies reported that the application of Bacillus spp., such as B. subtilis, B. cereus, Bacillus licheniformis, could manage diseases caused by Phytophthora species, such as Phytophthora capsici, P. sojae, Phytophthora fragariae var. fragariae, Phytophthora infestans, and Phytophthora cactorum on pepper, soybean, potato, cucumber, alfalfa, strawberry and apple (Utkhede 1984;Handelsman et al 1990;Osburn et al 1995;Anandhakumar and Zeller 2008;Özyilmaz and Benlioglu 2013;Maksimov et al 2014;Khabbaz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Different lowercase letters above the bars indicate significant difference between the treatments at P < 0.05 level by ttest Many studies reported that the application of Bacillus spp., such as B. subtilis, B. cereus, Bacillus licheniformis, could manage diseases caused by Phytophthora species, such as Phytophthora capsici, P. sojae, Phytophthora fragariae var. fragariae, Phytophthora infestans, and Phytophthora cactorum on pepper, soybean, potato, cucumber, alfalfa, strawberry and apple (Utkhede 1984;Handelsman et al 1990;Osburn et al 1995;Anandhakumar and Zeller 2008;Özyilmaz and Benlioglu 2013;Maksimov et al 2014;Khabbaz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, some species belong to the same genus as our identified species were confirmed to have positive effect on plant growth. For instance, some species of Bacillus, Pseudomonas, Acremonium and Humicola could promote plant growth due to their antagonistic activity, the production of IAA or specific substance to activate resistance for control of diseases (Dharni et al 2014;Hassan et al 2015;Khabbaz et al 2015;Wenhsiung 2009;Yang et al 2014). On the other side, some species of these genera showed negative effect on plant growth due to their broadspectrum pathogenic activity (Elbanna et al 2014;Furuya et al 2005;Iakovleva et al 2013;Racedo et al 2013;Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This exudate causes an increase in bacterial propagation of both pseudomonads and other benefi cial bacteria. Within the bacterial cells, there is an upregulation of the expression of phzI gene, resulting in an increased activity of N -acyl-Lhomoserine lactone or generally referred to as HSL (Khabbaz et al 2015 ;Schenk et al 2014 ). This ultimately leads to an increase in the production of PCA which inhibits the further colonization and propagation of the fungus on roots.…”
Section: Biocontrol and Antibiosismentioning
confidence: 99%